2010
DOI: 10.1007/s10336-009-0491-2
|View full text |Cite
|
Sign up to set email alerts
|

Is abdominal implantation of devices a good alternative to external attachment? A comparative study in Adélie penguins

Abstract: Bio-logging studies suffer from the lack of real controls. However, it is still possible to compare indirect parameters between control and equipped animals to assess the level of global disturbance due to instrumentation. In addition, it is also possible to compare the behaviour of free-ranging animals between individuals equipped with different techniques or instruments to determine the less deleterious approach. We instrumented Adélie Penguins (Pygoscelis adeliae) with internal or external time-depth record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Such wires and fixing sutures may increase the likelihood of device effects. Beaulieu et al [32] compared the effects of external (n = 10 animals) and internal (n = 6 animals) tags on the foraging behavior of Adelie penguins. They noted altered foraging behavior in animals carrying internal tags, but none in animals carrying external tags.…”
Section: Implanted Telemetry Devices In Birdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such wires and fixing sutures may increase the likelihood of device effects. Beaulieu et al [32] compared the effects of external (n = 10 animals) and internal (n = 6 animals) tags on the foraging behavior of Adelie penguins. They noted altered foraging behavior in animals carrying internal tags, but none in animals carrying external tags.…”
Section: Implanted Telemetry Devices In Birdsmentioning
confidence: 99%
“…Furthermore, device volume may be more closely related to altered body mass set points in some animals [83], and buoyancy may affect cost of locomotion more than mass [84,85]. Several researchers have suggested that implant size indices based on the percentage device weight in water or volume to body mass ratios should be preferable for aquatic vertebrates [13,17,19,31,32]. Beaulieu et al [32] specifically suggested using device volume per body mass (ml/kg) as a metric.…”
Section: Validate Safe Designs For Fitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, because of the invasiveness of surgical implantation and the time required for recovery/healing, which might affect performance, external attachment might be preferable for short-term deployments. For example, Beaulieu et al (2010) found that the dive performance of implanted Adélie penguins (Pygoscelis adeliae) during a single foraging trip (approximately 2 weeks) was significantly reduced when compared with penguins with external device attachment.…”
Section: Methodsmentioning
confidence: 99%
“…The severity of such a response will depend on the outer material of the implanted device and a surface coating with biocompatible material is, therefore, of great importance, as are proper sterilization procedures (Hawkins 2004;Bryers et al 2012;Mulcahy 2013). Depending on the species in question, device volume might affect body mass set points (Bradley 1978;Adams et al 2001), pressurize adjacent organs such as air sacs in birds (Beaulieu et al 2010), and even interfere with female reproduction (Horning et al 2017), while device mass and buoyancy might affect locomotion costs (Webb et al 1998;Schmidt-Wellenburg et al 2008). In diving species, problems from extensive pressurization might arise, damaging components of the device and, in the worst case, causing battery breakdown and leakage.…”
Section: Devicesmentioning
confidence: 99%